The variable structural flexibility of the Bacillus circulans β-galactosidase isoforms determines their unique functionalities - Hovorková, Michaela; Kaščáková, Barbora; Petrásková, Lucie; Havlíčková, Petra; Nováček, Jiří; Pinkas, Daniel; Gardian, Zdenko; Křen, Vladimír; Bojarová, Pavla; Smatanová, Ivana Kutá (Structure (London, England, 2024)
β-Galactosidase from Bacillus circulans ATCC 31382 (BgaD) is a biotechnologically important enzyme for the synthesis of β-galactooligosaccharides (GOS). Among its four isoforms, isoform A (BgaD-A) has distinct synthetic properties. Here, we present cryoelectron microscopy (cryo-EM) structures of BgaD-A and compare them with the known X-ray crystal structure of isoform D (BgaD-D), revealing substantial structural divergences between the two isoforms. In contrast to BgaD-D, BgaD-A features a flexible Big-4 domain and another enigmatic domain. The newly identified flexible region in BgaD-A is termed as "barrier domain 8," and serves as a barricade, obstructing the access of longer oligosaccharide substrates into the active site of BgaD-A. The transgalactosylation reactions catalyzed by both isoforms revealed that BgaD-A has a higher selectivity than BgaD-D in the earlier stages of the reaction and is prevailingly directed to shorter galactooligosaccharides. This study improves our understanding of the structural determinants governing β-galactosidase catalysis, with implications for tailored GOS production.
Keywords: izoenzymy; beta-galaktosidasa; transgalactosylation; Substrate Specificity; galactooligosaccharide; Cryoelectron Microscopy; substrate specificity; bakteriální proteiny; Bacterial Proteins; krystalografie rentgenová; Oligosaccharides; crystal structure; oligosacharidy; Models, Molecular; molekulární modely; katalytická doména; beta-Galactosidase; Protein Isoforms; structural flexibility; Bacillus; elektronová kryomikroskopie; protein - isoformy; Isoenzymes; Crystallography, X-Ray; substrátová specifita; cryo-EM; Catalytic Domain; galactosidase